Efficacy of Safinamide and Gender Differences During Routine Clinical Practice - Pellecchia, Maria T.; Picillo, Marina; Russillo, Maria C.; De Pandis, Maria F.; Bonizzoni, Erminio; Marjanovic, Ivan; Cattaneo, Carlo (Frontiers in Neurology, 2021)
Background: There is an increasing evidence of gender differences in the epidemiology and clinical manifestation of both motor and non-motor symptoms of Parkinson’s disease (PD). Nevertheless, few data are available on gender differences in the response to antiparkinsonian drugs. Safinamide is a multi-modal drug with positive effects on motor and non-motor fluctuations that might improve patients’ care and quality of life. Objective: To analyse gender differences on clinical effects of safinamide in PD patients treated in real-life conditions during the SYNAPSES trial. Methods: SYNAPSES was a multinational, multicenter, observational study. At baseline, patients with PD diagnosis received safinamide as add-on to levodopa and were followed for 12 months with visits performed every 4 months. A new statistical analysis was performed to describe the efficacy of safinamide in men and women on motor complications, motor symptoms and adverse events. Results: Six hundred sixteen (38%) out of 1610 patients enrolled in the SYNAPSES study were women and 994 (62%) men. Safinamide improved motor symptoms and motor complications (fluctuations and dyskinesia) in both genders, with a good safety profile and without requiring any change in the concomitant dopaminergic therapy. Clinically significant improvements, according to the criteria developed by Shulman et al., were seen in 46% of male and female patients for the UPDRS motor score and in 43.5% of men vs 39.1% of women for the UPDRS total score. Conclusions: Safinamide was effective in improving motor fluctuations and dyskinesia and proved to be safe in both male and female patients with PD. Further prospective studies specifically addressing potential gender differences in response to PD therapies are needed to develop tailored management strategies.